Physics for Scientists and Engineers : Foundations and Connections with Modern Physics - Katz, Debora M. (Cengage Learning)
Contenido: 1) Mecánica clásica; 2) Mecánica de sistemas complejos; 3) Electricidad; 4) Magnetismo; 5) Luz; 6) Física del siglo XX. Apéndices.